2021
DOI: 10.3390/diagnostics11081464
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Non-Invasive In Vivo Optical Diagnostics in the Assessment of Structural Changes in the Skin Induced by Ultraviolet Exposure in an Experimental Model

Abstract: Background: This paper demonstrates the use of optical diagnostic methods to assess the dynamic skin changes observed in acute and chronic exposure to ultraviolet (UV) radiation in vivo. Methods: Firstly, in order to initiate photoaging (chronic UV exposure), animals (n = 40) were divided into two groups: chronic UV exposure (n = 30), and control (n = 10; without irradiation). Photoaging in animals was induced by chronic repeated exposure to UVA radiation three times per week, for 12 weeks continuously, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Simple calculations show that when the skin is exposed to milliwatt-power UV radiation emitted by an optical fiber with a diameter of, for example, 100 microns, the MED value is exceeded even with a short-term exposure of a few seconds. However, from our practice with fiber optic diagnostic equipment in the UV range, the formation of erythema is not observed even during minutes of exposure [13]. To the best of our knowledge, there are no such reports about erythema formation from other researchers.…”
Section: Introductionmentioning
confidence: 94%
“…Simple calculations show that when the skin is exposed to milliwatt-power UV radiation emitted by an optical fiber with a diameter of, for example, 100 microns, the MED value is exceeded even with a short-term exposure of a few seconds. However, from our practice with fiber optic diagnostic equipment in the UV range, the formation of erythema is not observed even during minutes of exposure [13]. To the best of our knowledge, there are no such reports about erythema formation from other researchers.…”
Section: Introductionmentioning
confidence: 94%
“…In studies about skin diseases or damage, OCT is used in animal experiments. Kulikov et al showed that OCT images of photoaging in animal models correlated well with histological findings, validating the feasibility of the continuous OCT detection of photodamage [ 25 ]. However, only acute UV damage models were established that lacked the continuous observation of samples as well as highly specific immunohistochemical and immunofluorescence techniques.…”
Section: Introductionmentioning
confidence: 94%